Thermal Ablation and Transarterial Chemoembolization are Characterized by Changing Dynamics of Circulating MicroRNAs - Andrasina, Tomas; Juracek, Jaroslav; Zavadil, Jan; Cechova, Barbora; Rohan, Tomas; Vesela, Petra; Paldor, Mor; Slaby, Ondrej; Goldberg, S Nahum (Journal of vascular and interventional radiology, 2021)
PURPOSE: To determine whether the levels of circulating microRNAs (miRNAs) are altered in patients undergoing thermal ablation and chemoembolization and whether these changes are predictive of a clinical outcome. MATERIAL AND METHODS: This prospective study consisted of 43 patients diagnosed with hepatocellular carcinoma (n = 15) and intrahepatic colorectal cancer metastases (n = 28) treated with thermal ablation (n = 23; radiofrequency [n = 6] or microwave [n = 19]), chemoembolization using drug-eluting embolics (n = 18), or both (n = 2). Four blood samples (immediately before the intervention and 60-90 minutes, 24 hours, and 7 days after the intervention) were taken to measure the plasma concentrations of miRNAs related to hypoxia (miR-21 and miR-210), liver injury (miR-122), epithelial-mesenchymal transition (miR-200a), and apoptosis (miR-34a) using miRNA-specific TaqMan assays and quantitative real-time polymerase chain reaction. Tumor burden and treatment response at 3 months were evaluated using the modified response evaluation criteria in solid tumors. The miRNA results were compared with clinical outcomes (Mann-Whitney U test, Wilcoxon matched-pair test). RESULTS: Dynamic changes in the circulating miRNA levels were observed following both the interventions. For thermal ablation, significant increases in miR-21, miR-210, miR-122, miR-200a, and miR-34a concentrations peaked 60-90 minutes after the intervention (P < .01). However, for transarterial chemoembolization, maximum increases in the miRNA concentrations were observed at 24 hours after the intervention for miR-21, miR-210, miR-122, miR-200a, and miR-34a (P < .05). The increased concentrations of the circulating miRNAs were followed by a subsequent decline to baseline by 7 days. For the thermal ablation (but not chemoembolization) patients, elevations in the miR-210 and miR-200a levels were associated with early progressive disease at 3 months (P = .040 and P = .012, respectively). CONCLUSIONS: Increased but dynamic levels of circulating miRNAs are present following interventional oncologic procedures and may prove useful as biomarkers for the monitoring of clinical outcomes.
Keywords: Microwaves; kolorektální nádory; Female; Circulating MicroRNA; mikrovlny; hepatocelulární karcinom; výsledek terapie; ženské pohlaví; Colorectal Neoplasms; Time Factors; časové faktory; lidé; nádory jater; Carcinoma, Hepatocellular; Treatment Outcome; chemoembolizace; Liver Neoplasms; prospektivní studie; Male; nádorové biomarkery; Aged; Prospective Studies; radiofrekvenční ablace; Radiofrequency Ablation; Biomarkers, Tumor; lidé středního věku; senioři; mužské pohlaví; cirkulující mikroRNA; Middle Aged; Chemoembolization, Therapeutic; Humans